Potensi Bahaya Ergonomi Pada Pekerja PT Mega Andalan Kalasan (MAK) - Sukadi Sukadi; Fitriani Fitriani; Angelia Dina Aristasari (Pascasarjana Universitas Jember, 2022)
The World Health Organization (WHO) states that the top ten causes of death and illness worldwide are caused by occupational risks. In Indonesia itself in 2005, the Ministry of Health of the Republic of Indonesia stated that as many as 16% of workers had musculoskeletal complaints. The workers every day always do the same work and repeat from day to day, so it is feared that in the long term their health will be disturbed. Quoted from the Central Statistics Agency, the number of industrial sectors in DIY contributed 11.97% to regional income. One of the industrial companies in the Special Region of Yogyakarta (DIY) is PT Mega Andalan Kalasan (MAK). This research was conducted at PT Mega Andalan Kalasan (PT MAK) with a descriptive type of research. The potential for ergonomic hazards at PT Mega Andalan Kalasan (PT MAK) is a source of potential losses arising from the concept of work attitude, work station layout. Where this ergonomic hazard has the potential to occur to all workers at PT MAK without any difference in treatment. The potential hazards of ergonomics based on aspects of work attitude are found in the finishing process (fireplace and wheel refinement and small parts).